Silicon-Based Light Sources for Silicon Integrated Circuits. (3rd June 2008) - Pavesi, L.
Abstract : Silicon the material per excellence for electronics is not used for sourcing light due to the lack of efficient light emitters and lasers. In this review, after having introduced the basics on lasing, I will discuss the physical reasons why silicon is not a laser material and the approaches to make it lasing. I will start with bulk silicon, then I will discuss silicon nanocrystals andEr 3 + coupled silicon nanocrystals where significant advances have been done in the past and can be expected in the near future. I will conclude with an optimistic note on silicon lasing.